Language ideologies and the positioning of learners in a multilingual Grade 1 classroom: a case study - Layton, Laura (School of Education, 2014)
This study is motivated by the under theorization of language and the impact that perception and discourse about languages have on diverse language users in the classroom. It draws on the theoretical understanding of Bourdieu's linguistic capital, as well as language ideology and Critical Discourse Analysis (CDA). I argue that there is a link between the micro and macro-level discourses that circulate a specific type of language ideology that affects the positioning of diverse language users in the classroom. For the investigation of language ideologies and learner positioning, I observed a multilingual grade one classroom in a township school in the Cape Flats, South Africa for five weeks, and later interviewed the participating classroom teacher. I transcribed video-recorded data from the classroom as well as the teacher interview and used CDA for analysis. Supported by the analysis of my non-participant observations and interview of the classroom teacher, my study suggests that the discourses of languages as separate and bounded entities that must remain pure limit the teaching of language and literacy, and inhibit the students from using their full linguistic repertoire in the classroom, reducing students to deficient monolingual speakers. At the same time, discourse about students being deficient furthers their negative positioning. The teacher's language background plays a role in the way she connects with the children and the way that children are positioned. I conclude that macro-level discourses and perceptions of languages and students of diverse languages have a large impact on the micro-level context of a classroom. In order to create a more positive learning environment I suggest the need for teachers to have more exposure to theorization of language thereby gaining a better understanding of language, and an awareness of the impact of discourse on learner positioning in order for change to take place.